Integration of pronunciation practice into speaking activities: An action research at Hanoi Tourism College" = Nghiên cứu hành động về việc kết hợp kỹ năng phát âm trong các hoạt động nói tiếng Anh của sinh viên trường Cao đẳng Du lịch Hà Nội . M.A Thesis - Trần, Thị Thu Hà, 1989- (University of Languages and International Studies, 2017)
Speaking a second language involves different skills such as grammar, vocabulary, and so on. Pronunciation plays a very important role in English Language Teaching. This action research is an attemptto investigate the effects of the integration of pronunciation practice into speaking activities on the students‟ achievement in speaking skills and give some pedagogical implications for the non-major first year students at Hanoi Tourism College. On integrating pronunciation into speaking activities in oral lessons, we have discovered that activities structured by integrating pronunciation practice can help to improve students‟ intelligibility and achievement in speaking performance. In addition, some helpful techniques of integrating pronunciation into activities have been realized with a view to improve the quality of teaching the speaking skill